Argos e o animal anfíbio. Equívocos e acertos da interpretação que Pippin oferece da Estética de Hegel no livro After the Beautiful. Hegel and the Philosophy of Pictorial Modernism - Cecchinato, Giorgia (Revista Eletrônica Estudos Hegelianos, 2019)
My aim is to describe the content of Pippin’s work After the beautiful. Hegel and the philosophy of pictorial modernismand to show the misconceptions the American philosopher incurs. This is not just to argue for a "true" or more correct interpretation of Hegel's philosophy, I try instead to delve into some issues that may help to understand the relationship between art and freedom that Pippin places as central to his "application" of Hegel's thought to modern times.